Hemodynamic evaluation in patients with transposition of the great arteries after the arterial switch operation: 4D flow and 2D phase contrast cardiovascular magnetic resonance compared with Doppler echocardiography. Issue 1 (December 2016) - Jarvis, Kelly; Vonder, Marleen; Barker, Alex; Schnell, Susanne; Rose, Michael; Carr, James; Robinson, Joshua; Markl, Michael; Rigsby, Cynthia
Abstract Background Peak velocity measurements are used to evaluate the significance of stenosis in patients with transposition of the great arteries after the arterial switch operation (TGA after ASO). 4D flow cardiovascular magnetic resonance (CMR) provides 3-directional velocity encoding and full volumetric coverage of the great arteries and may thus improve the hemodynamic evaluation in these patients. The aim of this study was to compare peak velocities measured by 4D flow CMR with 2D phase contrast (PC) CMR and the gold standard Doppler echocardiography (echo) in patients with TGA after ASO. Methods Nineteen patients (mean age 13 ± 9 years, range 1–25 years) with TGA after ASO who underwent 2D PC CMR and 4D flow CMR were included in this study. Peak velocities were measured with 4D flow CMR in the aorta and pulmonary arteries and compared to peak velocities measured with 2D PC CMR and Doppler echo. 2D PC CMR data were available in the ascending aorta, main, right and left pulmonary arteries (AAO/MPA/RPA/LPA) for 19/18/17/17 scans, respectively, and Doppler echo data were available for 13/9/6/6 scans, respectively. Peak velocities were measured with: 1) a single cross section for 2D PC CMR, 2) velocity maximum intensity projections (MIPs) for 4D flow CMR and 3) Doppler echo. Results Significantly higher peak velocities were found with 4D flow CMR than 2D PC CMR in the AAO (p = 0.003), MPA (p = 0.002) and RPA (p = 0.005) but not in the LPA (p = 0.200). No difference in peak velocity was found between 4D flow CMR and Doppler echo (p > 0.46) or 2D PC CMR and echo (p > 0.11) for all analyzed vessel segments. Conclusions 4D flow CMR evaluation of patients with TGA after ASO detected higher peak velocities than 2D PC CMR, indicating the potential of 4D flow CMR to provide improved stenosis assessment in these patients.